Middle powers trade policy. Why international political economy needs to pay closer attention to it - Albertoni, Nicolás (Estudios Internacionales, 2025)
As the international system continues its shift toward multipolarity, middle powers are playing increasingly prominent and proactive roles in shaping global trade governance. This article argues for the inclusion of middle powers' trade strategies as a critical new dimension in International Political Economy (IPE) research. It first offers a comprehensive theoretical overview of the middle power concept, highlighting its evolution and definitional debates. It then presents a comparative analysis of middle power trade diplomacy through case studies from different regions, than can be study by further research. Finally, it explores how these actors are contributing to reshaping global trade architecture and why their strategies deserve deeper attention in IPE scholarship. In doing so, this study contributes to a broader understanding of how normative, diplomatic, and coalition-building capabilities intersect with trade policy to define the agency of middle powers in the 21st century.